Leadership Style in Character Education at The Darussalam Gontor Islamic Boarding - M. Ihsan Dacholfany (Al-Ulum, 2015)
Pesantren (Islamic Boarding) is the oldest educational institution in Indonesia which has a role in character education. The main purpose of this study was to understand leadership style of teachers (clerics) in character education as well as the process to produce competent believers. Religio-paternalistic leadership is based on the value of total admission of religious and educational methods, with emphasis on the application of knowledge resulting believers’ faith and fear of Allah guided by the Qur'an and Sunnah. To obtain data, the author employed interview, observation and documenter. The Darussalam Gontor Islamic Boarding School in East Java was the field-site of this research.